Key competencies in sustainability in higher education—toward an agreed-upon reference framework - Brundiers, Katja; Barth, Matthias; Cebrián, Gisela; Cohen, Matthew; Diaz, Liliana; Doucette-Remington, Sonya; Dripps, Weston; Habron, Geoffrey; Harré, Niki; Jarchow, Meghann; Losch, Kealalokahi; Michel, Jessica; et al. (Sustainability science, 2021)
Hundreds of sustainability programs have emerged at universities and colleges around the world over the past 2 decades. A prime question for employers, students, educators, and program administrators is what competencies these programs develop in students. This study explores convergence on competencies for sustainability programs. We conducted a Delphi study with 14 international experts in sustainability education on the framework of key competencies in sustainability by Wiek et al. (Sustain Sci 6: 203–218, 2011), the most frequently cited framework to date. While experts generally agreed with the framework, they propose two additional competencies, suggest a hierarchy of competencies, and specify learning objectives for students interested in a career as sustainability researcher. The refined framework can inform program development, implementation, and evaluation to enhance employability of graduates and facilitate comparison of sustainability programs worldwide.